Differences in the endoscopic closure of colonic perforation due to diagnostic or therapeutic colonoscopy. (July 2013) - Magdeburg, Richard; Sold, Moritz; Post, Stefan; Kaehler, Georg
Abstract Objective. To describe the experience of a single center regarding the feasibility of endoscopic closure of iatrogenic colonic perforations and to elucidate differences between the efficacy of endoscopic clip closure due to diagnostic or therapeutic colonoscopy. Material and methods. A retrospective institutional computer-based search of records of colonoscopic perforation occurring between January 2004 and December 2011 was undertaken. Data on patients undergoing colonoscopy were entered into a clinical database. To further improve the detection of all cases of colon perforations, the authors also searched their separate surgical database for every patient with a colon perforation treated or operated on in the surgery department. Statistical significance was tested using either Fortran-Subroutine Fytest, chi-square testing or t-test. Results. Over 8 years, 22, 924 patients underwent colonoscopy, of which 105 consecutive patients suffered iatrogenic perforation. Clip application was possible in 62 patients (81.58%) after perforation due to a therapeutic colonoscopy, whereas clip application was only possible in 9 patients (31.03%) after perforation due to a diagnostic colonoscopy. 4 out of 9 patients (44.44%) in the diagnostic group compared with 7 out of 62 patients (11.29%) after clipping a perforation during a therapeutic colonoscopy were sent to surgery. Conclusions. The authors' data indicate significant differences in the potential for and success of endoscopic closure of iatrogenic perforations occurring during diagnostic or therapeutic colonoscopy. The frequency of surgery was significantly greater after clipping a perforation during a diagnostic colonoscopy.